Motion and sound games model for improving cognition of early childhood - Raden Roro Sriwidaningsih; Gita Febria Friskawati (Jurnal Cakrawala Pendidikan, 2022)
The early childhood stage is a phase that holds important basic development holistically, covering affective, psychomotor, and especially cognitive domains. This development will be able to be effectively reached with an appropriate learning process in kindergartens. This study aims to reveal a relevant approach to learning using motion and sound games in improving early childhood cognitive development. The method used in this study is Research and Development (RD) from Borg and Gall, involving 124 early childhoods and kindergarten teachers in the city of Cimahi, Indonesia, selected through convenience sampling. The instruments employed are questionnaires, observation notes, interviews, and desk evaluations (expert and practitioner judgment). The data are descriptively calculated through a t-test with p0.000 in order to reveal the learning model for improving children’s cognition through motion and sound. The results of this study show that the motion and sound–based models consist of design planning, learning process, and evaluation that are able to be implemented well and can be categorized as a model that is able to develop early childhood cognition, but it still needs to be innovated and continue to be creative again in more affordable learning steps for children. Studies with the related topics are expected to relate basic potentials and social skill optimization. It is also recommended that this study contributes to the development of learning in Indonesia